Initial approach to Epidermal Growth Factor in SARS-CoV-2 infection - Héctor José Pérez Hernández (Revista Cubana de Medicina Militar)
Introduction: Epidermal growth factor (EGF) receptor plays a critical role in lung inflammation. Data exploring the role of its canonical ligand are scarce. Exploring potential and new biomarkers expands diagnostic and therapeutic options, providing resilience in complex healthcare contexts. Objective: To describe the behavior of serum epidermal growth factor levels and evaluate its possible impact in the context of patients hospitalized with COVID-19. Methods: Controlled exploratory study with quota sampling, in patients with COVID-19 admitted at the "Saturnino Lora Hospital", and 23 apparently healthy subjects, active donors of Blood Bank "Renato Guitar Rosell". For EGF determinations, the commercial UMELISA EGF kit from the Cuban Immunoassay Center was used. Summary measures: absolute frequency, percentage, and the arithmetic mean were used. The statistical significance of observable differences between groups was explored with the chi-square test or Welch's t test with α= 0.05. Results: 46 subjects enrolled in the study, (23) 50% positive for SARS-CoV-2 by RT-PCR. Between COVID-19 vs. control, general differences were observed regarding epidermal growth factor (g=1.4465; p= 0.0000*), similar behavior was observed with respect to sex and age. In COVID-19 regarding severity, slight differences were generally observed depending on severity (g= 0.2152), a trend that was accentuated in the case of males (g= 1.1677) and females (g= 0.7533), the latter comparatively minor. Conclusions: Determining serum EGF in patients infected by SARS-CoV-2 could have a predictive value for severity in patients with COVID-19.